The role of counselors in shaping students' self-happiness in inclusive schools - Azwar, Beni; Hartini, Hartini; Syafril, Syafrimen (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
This study aims to look at the role of counselors in shaping students' self-happiness in inclusive schools at Muhammadiyah Curup junior high school. Self-happiness is an important thing that must exist in inclusive group rooms; therefore, counselors need to understand the characteristics of students to unite normal children and children with special needs with the same curriculum and learning process. In inclusive schools, it is found that bullying of children with special needs still occurs, and the learning process in inclusive groups is relatively slow and constrained, making ordinary students bored and upset. The approach used is qualitative with a grounded theory design. The data will be interpreted in a naturalistic way to overcome the problems in this study. Data interpretation and a naturalistic approach will provide answers related to the counselor's role in developing students' self-happiness in the inclusion group of Muhammadiyah Curup junior high school. The research subjects were counselors, subject teachers, principals, normal children, children with special needs, and parents of children with special needs. Data collection was done voluntarily by building good interactions without coercion and carefully selecting informants. Data were analyzed using three levels of analysis: open coding (forming categories of information about the event or phenomenon under study), axial coding (solving for core themes during qualitative data analysis), and selective coding (selective coding to find significant categories). The results revealed that the role of counselors is to build collective consciousness with the quality and quantity of empathy, positive relationships, emotional attachment and connection, and meaningfulness of life for oneself and others.